A Case of Neurologically Intact Survival after Compression-Only Cardiopulmonary Resuscitation by Two Bystanders. Issue 6 (November 2016) - Chen, HC; Hung, YM; Hsieh, FC; Lin, SL
Conventional cardiopulmonary resuscitation (CPR) requires chest compression and mouth-to-mouth breathing. We report a 55-year-old man in cardiac arrest who received immediate chest compression but without assisted ventilation by two bystanders for 28 minutes until the arrival of the emergency medical team. His consciousness recovered completely on the third hospital day. According to the literature review, "28 minutes" may possibly be the longest period of time of compression-only CPR in out-of-hospital cardiac arrest patients with neurologically intact survival. Thus, this case supports the present CPR guideline that recommends effective chest compression without assisted ventilation by laypersons for patients in cardiac arrest.